An analysis of factors influencing electric vehicle uptake among ride-hailing drivers in Malang Raya, East Java, Indonesia - Tri Wulida Afrianty; Kusdi Raharjo; Yudha Prakasa; Anggito Abimanyu (Cogent Business & Management)
This study investigates the factors influencing the adoption of electric vehicles (EVs) among ride-hailing drivers in Malang Raya, East Java, Indonesia. Utilizing an integrated theoretical framework combining the Diffusion of Innovation Theory, the Theory of Planned Behavior, and the Unified Theory of Acceptance and Use of Technology (UTAUT), this research aims to analyze EV adoption’s determinants. Data were collected from 436 ride-hailing drivers through an online survey and analyzed using PLS-SEM. The findings reveal that self-efficacy, facilitating conditions and product knowledge significantly enhance perceived behavioral control, positively affecting purchase intention. Moreover, perceived behavioral control mediates the relationships between all three predictors and purchase intention, emphasizing its critical role in EV adoption. The inclusion of demographic data as control variables further reveals that gender has a significant negative effect, while age shows a positive influence on purchase intention. However, education does not significantly affect purchase intention. These results highlight the importance of increasing user confidence, improving supportive infrastructure, and enhancing product knowledge to foster EV adoption. The study offers valuable insights for policymakers and stakeholders in Malang Raya and similar contexts. By addressing technological and behavioral factors, this research promotes sustainable transportation and environmental conservation efforts in the region.